Advanced system‐level simulation paradigm for ultra‐wideband systems using SCERNE platform. Issue 12 (30th September 2019) - Ojaroudi, Mohammad; Bila, Stephane; Ngoya, Edouard; Mons, Sebastien; Torrès, François; Beaumont, Arnaud; Lintignat, Julien
Abstract: In this article, a progressive system‐level simulation framework is developed based on Simulation de Chaînes d'Emission/Réception Nouvelle gEnération (SCERNE) platform to simulate an ultra‐wideband (UWB) impulse radar transmitter and accurately predict its performance. With the purpose of demonstrating the usefulness of the SCERNE ability in system‐level modeling, we present and simulate a simplified structure of UWB impulse radar transmitter. First, after simulation each component in different circuit‐level tools such as ADS, CST, and HFSS, each part has been modeled by using different modeling methods to transfer their data into MATLAB environment. Then, we duplicate the transmitter structure in SCERNE toolbox to validate the results. The advantage conferred by the proposed SCERNE toolbox is that fast and accurate bilateral modeling method is available at multi‐medium structures in contrast with conventional unilateral modeling, and so a lower memory and higher accuracy of the behavioral model is achieved. It can also be beneficial when the user is looking for system‐level, as the increased components amounts can help as a surrogate model. The system model can be easily extended to other UWB radar systems by simply changing the input pulse shape, UWB channel environment, transceiver topology, etc. Various effects such as signal quality, and pulse shape that can easily investigate and re‐optimize for high performance are using the developed model. To validate the practicality of the proposed paradigm, the simulations and predictions through model results are being outlined.